Ecological Interactions of Cyanobacteria and Heterotrophs Enhances the Robustness of Cyanobacterial Consortium for Carbon Sequestration - Ataeian, Maryam; Liu, Yihua; Kouris, Angela; Hawley, Alyse K.; Strous, Marc (Frontiers in Microbiology, 2022)
Lack of robustness is a major barrier to foster a sustainable cyanobacterial biotechnology. Use of cyanobacterial consortium increases biodiversity, which provides functional redundancy and prevents invading species from disrupting the production ecosystem. Here we characterized a cyanobacterial consortium enriched from microbial mats of alkaline soda lakes in British Columbia, Canada, at high pH and alkalinity. This consortium has been grown in open laboratory culture for four years without crashes. Using shotgun metagenomic sequencing, twenty-nine heterotrophic metagenome-assembled-genomes (MAGs) were retrieved and were assigned to Bacteroidota, Alphaproteobacteria, Gammaproteobacteria, Verrucomicrobiota, Patescibacteria, Planctomycetota, and Archaea. In combination with metaproteomics, the overall stability of the consortium was determined under different cultivation conditions. Genome information from each heterotrophic population was investigated for six ecological niches created by cyanobacterial metabolism and one niche for phototrophy. Genome-resolved metaproteomics with stable isotope probing using 13C-bicarbonate (protein/SIP) showed tight coupling of carbon transfer from cyanobacteria to the heterotrophic populations, specially Wenzhouxiangella. The community structure was compared to a previously described consortium of a closely related cyanobacteria, which indicated that the results may be generalized. Productivity losses associated with heterotrophic metabolism were <20% compared to other losses during photosynthesis.